PETA GERAKAN SYIâAH DI KALIMANTAN SELATAN - humaidy, Humaidy (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
This article traces back the entry of the Shiâa in South Kalimantan through the inclusion of Islamic Wujudiyah (panentheism) Sufismwhich was firstspreadin the kingdom of Banjar. Â This isdue to the similaritybetween Wujudiyah Sufism with the concept of Irfan in Shia. However, the influence of Shia in Â South KalimantanÂ  suffered a setback atthe era Â of Syekh Muhammad al-Banjari Arsyad (1710-1812 AD). Â According to Habib Ali,Shia began to revive in South Kalimantan after the Iranian revolution in 1979. Â Jaâfari school of thought (madhabs)Â  is the growing Shiah in South Kalimantan. The Developmentof Shiâa in South kalimantan faces manychallenges since Muslims in South Kalimantan have a strong belief in Sunni